Аналитическое определение геометрических параметров очага деформации при прокатке фланцевых профилей. Сообщение 2 - Медведев, В. С.; Шпаков, В. А.; Базарова, Е. В. (НТУ "ХПИ", 2013)
Приведена методика аналитического определения геометрических параметров очага деформации при прокатке фланцевых профилей в калибрах с открытыми и закрытыми ручьями. Путем совместного решения уравнений поверхностей вращения валков и плоских поверхностей заготовки получены общие аналитические выражения для расчета координат граничных точек очага деформации. Методика может быть использована при создании универсальной математической модели прокатки фасонных профилей

The technique of analytical determination of geometrical parameters in the center of deformation is given when rolling flange profiles in calibers with the opened and closed strands. By the joint solution of the equations of surfaces of rotation of rolls and flat surfaces of preparation the general analytical expressions for calculation of coordinates of boundary points of the center of deformation are received. The technique can be used at creation of universal mathematical model of rolling of shaped profiles. Im.:4 DBMS is drawn is developed
Keywords: контур; калибр; станки с ЧПУ; арматура; шаблон; течение металла; flange profile; rolling; center of deformation; geometrical parameters